Penerapan Framework Laravel Pada Sistem Jurnal Lab Komputer Di SMK PGRI Rogojampi - Uchrowiya, Latifatul; Alfiyan, Faruk (Jurnal Informatika dan Komputer, 2025)
The computer laboratory is a vital facility for technology-based learning and practical activities in education, ranging from high school to university level. However, scheduling conflicts often arise when multiple groups need access to the lab at the same time. This is mainly due to the fact that scheduling and activity reporting are still managed manually. Such a system frequently causes inefficiencies and disrupts the workflow. To address this issue, a web-based computer lab journal system needs to be developed. This system is designed using the Hypertext Preprocessor (PHP) programming language with the Laravel framework, and it uses MySQL as its database. The system development follows the waterfall model. With this solution, lab management is expected to become easier, more organized, and better able to support learning through a computerized approach.